2017
DOI: 10.3389/fcimb.2017.00466
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Responses of Multidrug-Resistant Pseudomonas aeruginosa and Acinetobacter baumannii Following Exposure to the Antimicrobial Peptide Cathelicidin-BF Imply Multiple Intracellular Targets

Abstract: Cathelicidin-BF, derived from the banded krait (Bungarus fasciatus), is a typically cationic, amphiphilic and α-helical antimicrobial peptide (AMP) with 30 amino acids that exerts powerful effects on multidrug-resistant (MDR) clinical isolates, including Pseudomonas aeruginosa, Acinetobacter baumannii, and Klebsiella pneumoniae, but whether it targets plasma membranes or intracellular targets to kill bacteria is still controversial. In the present study, we demonstrated that the disruption of bacterial membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…These studies were carried out as we previously reported with slight modifications and briefly introduced as follows ( Liu et al, 2017 ). Serum stability was assessed with increases over the minimal inhibitory concentration (MIC) of tachyplesin III (KW C FRVCYRGICYRK C R; cysteines with the same type font formed on disulfide; purity ≥ 95%, synthesized by GL Biochem Co., Ltd, Shanghai, China) on Escherichia coli strain DH5α after incubation in serum.…”
Section: Methodsmentioning
confidence: 99%
“…These studies were carried out as we previously reported with slight modifications and briefly introduced as follows ( Liu et al, 2017 ). Serum stability was assessed with increases over the minimal inhibitory concentration (MIC) of tachyplesin III (KW C FRVCYRGICYRK C R; cysteines with the same type font formed on disulfide; purity ≥ 95%, synthesized by GL Biochem Co., Ltd, Shanghai, China) on Escherichia coli strain DH5α after incubation in serum.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that AMPs achieve antimicrobial activity by disrupting various key microorganism cell processes, with some AMPs possessing multiple mechanisms (Brogden, 2005; Nguyen et al, 2011). There are many specific targets in microbial cells for AMPs, including external proteins, outer surface lipids, outer membrane proteins (gram-negative bacteria), inner membrane, integral membrane proteins, nucleic acids and intracellular proteins (Liu et al, 2017, 2018; Nguyen et al, 2011). Among them, disrupting the integrity of the microbial inner membrane is the most common mode for AMPs (Liu et al, 2017, 2018; Nguyen et al, 2011), the disruption of which results in obvious morphological alteration.…”
Section: Resultsmentioning
confidence: 99%
“…There are many specific targets in microbial cells for AMPs, including external proteins, outer surface lipids, outer membrane proteins (gram-negative bacteria), inner membrane, integral membrane proteins, nucleic acids and intracellular proteins (Liu et al, 2017, 2018; Nguyen et al, 2011). Among them, disrupting the integrity of the microbial inner membrane is the most common mode for AMPs (Liu et al, 2017, 2018; Nguyen et al, 2011), the disruption of which results in obvious morphological alteration. Here, the antimicrobial results showed that S. aureus ATCC25923 was most sensitive to amurin-9KY, and therefore it was selected to examine the induced membrane morphological alterations by SEM.…”
Section: Resultsmentioning
confidence: 99%
“…Second, at concentrations near the MIC, As-CATH8 showed only modest effects on the membranes, while peptide internalization and intracellular signaling may still have occurred at these concentrations. Interaction with bacterial DNA has been shown to be important for the antimicrobial mechanism of several vertebrate cathelicidins, including LL-37 [ 46 , 47 , 48 ]. This interaction can potentially interfere with several bacterial processes, such as replication and transcription, and usually leads to bacterial death [ 47 , 49 ].…”
Section: Discussionmentioning
confidence: 99%